Mask wearing in Japanese and French nursery schools: The perceived impact of masks on communication - Crimon, Cécile; Barbir, Monica; Hagihara, Hiromichi; de Araujo, Emma; Nozawa, Sachiko; Shinya, Yuta; Abboub, Nawal; Tsuji, Sho (Frontiers in Psychology, 2022)
Due to the global COVID-19 pandemic, covering the mouth region with a face mask became pervasive in many regions of the world, potentially impacting how people communicate with and around children. To explore the characteristics of this masked communication, we asked nursery school educators, who have been at the forefront of daily masked interaction with children, about their perception of daily communicative interactions while wearing a mask in an online survey. We collected data from French and Japanese nursery school educators to gain an understanding of commonalities and differences in communicative behavior with face masks given documented cultural differences in pre-pandemic mask wearing habits, face scanning patterns, and communicative behavior. . Participants (177 French and 138 Japanese educators) reported a perceived change in their own communicative behavior while wearing a mask, with decreases in language quantity and increases in language quality and non-verbal cues. Comparable changes in their team members’ and children’s communicative behaviors were also reported. Moreover, our results suggest that these changes in educators’ communicative behaviors are linked to their attitudes toward mask wearing and their potential difficulty in communicating following its use. These findings shed light on the impact of pandemic-induced mask wearing on children’s daily communicative environment.